Principles of Terahertz Science and Technology - Lee, Yun-Shik (Springer, 2017)
Principles of Terahertz Science and Technology aims to elucidate the fundamentals of THz technology and science for potential new users. It surveys major techniques of generating, detecting, and manipulating THz waves and also discusses a number of essential processes where THz waves interact with physical, chemical, and biological systems. This book serves as an introduction to THz technology for new researchers in various fields.Many different disciplines, such as ultrafast spectroscopy, semiconductor device fabrication, bio-medical imaging and more, involve the recent development of THz technology. It is necessary to lay down a strong, common foundation among researchers, so that communication can proceed smoothly. Previous THz research activities have concentrated on generation and detection, but the focus has now shifted to practical applications of this technology, such as high-speed optoelectronic signal processing and molecular spectroscopy.Drawing upon years of practical experience and using numerous examples and illustrative applications Yun-Shik Lee discusses:The major techniques of generating, detecting, and manipulating THz wavesEssential processes where THz waves interact with physical, chemical, and biological systems Medical Applications of T-Ray Imaging including, optical properties of human tissue, cancer diagnostics, reflective imaging of skin burns and detection of dental cariesPrinciples of Terahertz Science and Technology is an ideal book for applied physicists, microwave engineers, biomedical engineers, electrical engineers, and analytical chemists interested in the fundamentals and applications of THz engineering